2018
DOI: 10.3126/jnspoi.v2i2.23615
|View full text |Cite
|
Sign up to set email alerts
|

Pain Perception after Periodontal Therapies

Abstract: Background: Pain perception is a complex sensory experience which is perceived by different individuals in different manners. The pain perceived by the patient after periodontal surgery may vary based on different parameters. Aim: This observational study was conducted to evaluate the perception of pain after periodontal therapies. Materials and Methods: A total of 63 surgeries were carried out in 50 patients and the surgeries were divided into three categories: open flap debridement, resective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The outcome of the study exhibited that pain scores using VAS did not show significant differences with the stages and grades of periodontitis. A similar outcome was also observed in the previous studies [ 19 , 28 ]. However, some studies on periodontal pain did not assess pain perception with periodontal conditions [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The outcome of the study exhibited that pain scores using VAS did not show significant differences with the stages and grades of periodontitis. A similar outcome was also observed in the previous studies [ 19 , 28 ]. However, some studies on periodontal pain did not assess pain perception with periodontal conditions [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…The current study used the VAS for assessing the pain perception of patients after the SRP treatment which is one of the most common tools measuring pain used in many previous studies not only in periodontal treatment but also in other branches of dentistry [ 2 , 15 , 19 , 28 , 31 ]. Another pain-assessing tool numeric rating scale (NRS) also been used in different studies [ 4 , 9 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The VAS scores were close to zero in all groups at the end of the study. Consistent with previous studies, this study demonstrated that a majority of patients exhibited mild pain perception during the first week of recovery following open flap debridement and pain was generally well tolerated (29)(30)(31). However, in the study of Canakci et al (23), which was inconsistent with the findings of our study, a higher pain perception was reported in patients receiving open flap debridement.…”
Section: Discussionsupporting
confidence: 72%
“…Hence, the use of longer acting local anesthetics may be considered in such situations. As reported earlier, periodontal surgeries produce less morbidity and discomfort to the patient (12). Therefore, second surgery was performed one week after the first surgery depending on the patients' comfort.…”
Section: Discussionmentioning
confidence: 99%